Impacts of fracturing fluid viscosity and injection rate variations on the fracture network propagation in deep coalbed reservoirs - Chang Sun; Yuan Zhang; Lishijia Han; Mengping Liu; Jinghong Hu (AIP Advances, 2025)
Adjusting the fracturing fluid viscosity and injection rate effectively enhances complex fracture network generation and increases stimulated reservoir volume (SRV). However, the underlying mechanical mechanisms still remain critically underexplored. Therefore, the objective of this study is to develop an effective fracture intersection criterion, which can systematically evaluate factors affecting fracture propagation and reservoir stimulation efficiency. We first studied the mechanical conditions during fracture intersection for the unique hydraulic fracture-cleat system of coalbed reservoirs and then established the fracture intersection criterion. The suitable fracturing parameters were obtained as well. Finally, a series of simulations were conducted to verify the fracture intersection criterion using the typical parameters in Block M. Results demonstrate that in the early period of fracturing, increasing the fracturing fluid viscosity and injection rate facilitates hydraulic fracture across the cleat, enhancing main fracture propagation and extending the fracture network length. The optimal parameters comprise an approach angle of 45°–60°, fracturing fluid viscosity higher than 65 mPa·s, and injection rate above 18 m3/min. In later fracturing, controlling the fluid viscosity and injection rate promotes cleats capturing hydraulic fractures, stimulating branch fracture generation and expanding the fracture network width. An approach angle of 45°–60°, fracturing fluid viscosity of 45–55 mPa·s, and injection rate of 16 m3/min are better in the late period. This scheme achieved an increase of 39.95% and 5.78% in the coverage area of the fracture network and SRV, illustrating a significant enhancement in reservoir stimulation efficiency. This study provides certain theoretical basis and parameter optimizations for improving the hydraulic fracturing performance.